Quality of life and its relationship to psychosocial adjustment among players with special needs - A field study on the Noor wheelchair basketball team in M'sila- - aimeur, mounira (Journal of Social Sciences and Humanities, 2023)
The study aimed to identify the reality of both the quality of life and the psychosocial compatibility of the players of the Noor wheelchair basketball team in M'sila state by measuring the level of each of them as well as knowing the relationship between them. For this purpose, the researcher relied on the descriptive approach to verify the research objectives as well as to confirm the validity of the hypotheses through the use of both the quality of life scale designed by the World Mental Health Organization and the psychological compatibility scale prepared by Ijlal Mohammed Serry .after checking their validity, they were applied to a sample of 15 players representing the Noor basketball team.